BOARDING MANAGEMENT DEVELOPMENT IN ISLAMIC RELIGIOUS EDUCATION - Nazirwan Nazirwan; Nur Cahaya; Junaidi Junaidi; Nofriyanti Nofriyanti (International Journal of Southeast Asia, 2020)
Boarding school is one of the oldest education institution in the national education system. Pesantren functions as a center for the spread of Islam, with a concentration of education in shaping Muslim people with a high understanding of three main problems, namely God, humans, and nature. Regarding its function as an educational institution, the aim of the Pesantren is to form individuals who excel in the field of understanding and practicing Islamic teachings for students or students in their daily lives. therefore it is necessary to have a good management of Pesantren in the development of Islamic religious education. Therefore, through this paper, the author wants to reveal how good management of Islamic boarding schools is in the development of Islamic religious education in the regional office of the Ministry of Religion of Jambi province. To obtain data that supports this article, the author uses a qualitative-naturalistic approach. Through this qualitative approach, it is hoped that a picture of the quality, social reality and perceptions of the research objectives will be exposed without being contaminated by formal measurements. So it can be concluded that there are several obstacles and recommendations for solutions in the management of Pesantren in the development of Islamic religious education in the regional office of the Ministry of Religion of Jambi province.